(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2014)
An Act to consolidate and amend the law relating to juveniles in conflictwith law and children in need of care and protection, by providing for propercare, protection and treatment by catering to their development needs, and byadopting a child-friendly approach in the adjudication and disposition ofmatters in the best interest of children and for their ultimate rehabilitationthrough various institutions established under this enactment. WHEREAS theConstitution has, in several provisions, including clause (3) of article 15,clauses (e) and (f) of article 39, articles 45 and 47, impose on the State aprimary responsibility of ensuring that all the needs of children are met andthat their basic human rights are fully protected; AND WHEREAS, the GeneralAssembly of the United Nations has adopted the Convention on the Rights of theChild on the 20th November,1989; AND WHEREAS, the Convention on the Rights of the Child has prescribed aset of standards to be adhered to by all State parties in securing the bestinterests of the child; AND WHEREAS, the Convention on the Rights of the Childemphasizes social reintegration of child victims, to the extent possible,without resorting to judicial proceedings; AND WHEREAS, the Government of Indiahas ratified the Convention on the 11th December, 1992; AND WHEREAS, it is expedientto re-enact the existing law relating to juveniles bearing in mind thestandards prescribed in the Convention on the Rights of the Child, the UnitedNations Standard Minimum Rules for the Administration of Juvenile Justice, 1985(the Beijing rules), the United Nations Rules for the Protection of JuvenilesDeprived of their Liberty (1990), and all other relevant internationalinstruments. Be it enacted by Parliament in the Fifty-first Year of theRepublic of India as follows:-